The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1021/jo200666z
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II)-Catalyzed Direct Alkenylation and Arylation of Arenes: Removable 2-Pyridylsulfinyl Group Assisted C–H Bond Activation

Abstract: Palladium-catalyzed C-H activation reactions directed by a removable 2-pyridylsulfinyl group were developed. Aromatic olefination products were formed in good yields on treatment of 2-(phenylsulfinyl)pyridines with alkenes in the presence of a Pd catalyst. The reaction tolerates a wide range of substituted alkenes, including various acrylates and styrenes. The controlled experiments indicated that the 2-pyridyl moiety, rather than the sulfinyl, played the role of ligand. The final reductive desulfonylation aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(27 citation statements)
references
References 61 publications
0
25
0
1
Order By: Relevance
“…However, the oxidative alkenylation of heteroarenes is named the Moritani-Fujiwara reaction. [8,9] In this regard, different palladium [10][11][12][13] and rhodium catalysts [14][15][16] have already been used to promote the oxidative alkenylation of heteroarenes with a variety of directing groups, namely, imines, [17,18] amines, [19] and carboxylates. [20,21] Rutheniumcatalyst-directed arylation of unactivated C-H bonds with phenols was reported by Ackermann.…”
Section: Introductionmentioning
confidence: 99%
“…However, the oxidative alkenylation of heteroarenes is named the Moritani-Fujiwara reaction. [8,9] In this regard, different palladium [10][11][12][13] and rhodium catalysts [14][15][16] have already been used to promote the oxidative alkenylation of heteroarenes with a variety of directing groups, namely, imines, [17,18] amines, [19] and carboxylates. [20,21] Rutheniumcatalyst-directed arylation of unactivated C-H bonds with phenols was reported by Ackermann.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang and co-workers showed that such intermediates enable the C À H/C À H coupling of arenes 30 with electron-deficient alkenes,s tyrenes,a nd arenes (Scheme 13 C). [25,26] Furthermore,t he 2-pyridylsulfinyl directing group has also been employed by Arrayµs,F ernµndez-Ibµnez, Carretero,a nd co-workers to mediate aP d II -catalyzed C À Hc oupling of 30 with methylboronic acid and aryl boronic acid neopentyl esters (Scheme 13 D). [27] Antonchick and Samanta employed as ulfoxide as the directing group in ap owerful Pd-catalyzed triple CÀH activation approach for the conversion of aryl benzyl sulfoxides 33 into important dibenzothiophenes 34.…”
Section: Sulfoxide-directed Transition-metal-catalyzedmentioning
confidence: 99%
“…Zhang und Mitarbeiter zeigten, dass derartige Intermediate eine C-H/C-H-Kupplung der Arene 30 mit elektronenarmen Alkenen, Styrolen und Arenen ermçglichen (Schema 13 C). [25,26] Darüber hinaus wurde die 2-Pyridylsulfinyl-Gruppe von Arrayµs,F ernµndez-Ibµnez, Carretero und Mitarbeitern als dirigierende Gruppe eingesetzt, um eine Pd II -katalysierte C-H-Kupplung von 30 mit Methylboronsäure und Arylboronsäureneopentylestern zu vermitteln (Schema 13 D). [27] Antonchick und Samanta gebrauchten ein Sulfoxid als lenkende Gruppe in einer beeindruckenden Pd-katalysierten dreifachen C-H-Aktivierung,welche die Arylbenzylsulfoxide 33 in die wichtigen Dibenzothiophene 34 umwandelt.…”
Section: Sulfoxid-gelenkte üBergangsmetallkatalysierte C-h-aktivierungunclassified